ANALISIS POTENSI LAHAN DAN STRATEGI PENGEMBANGAN SAWAH BARU SECARA BERKELANJUTAN DI KECAMATAN JATIGEDE, KABUPATEN SUMEDANG, PROVINSI JAWA BARAT - Santosa Raharjo; Santun R. P. Sitorus; Suwandi Suwandi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
The landuse change from paddy field to non-rice field in Java is increasing every year and this has an impact on the decreasing of national food security. Likewise the occurrence of land conversion of around 2,000 ha for the construction of Jatigede reservoir in Sumedang Regency, West Java Province has an impact on the decrease of rice production about 24 thousand tons of GKG (assuming rice productivity 6 ton/ha). The development of new sustainable rice fields is one of the solutions to improve food security and sustainability in the future both in Sumedang and Indonesia. The objectives of this research are: 1) to analyze the availability and suitability of land for the development of new paddy fields; 2) to analyze environmental feasibility and cost (environmental cost) in new rice field development activities; 3) analyze farmer institutional support in new rice field development activities; 4) to formulate the direction of new rice field development plan; and 5) to formulate a new rice field development strategy in Jatigede sub-district. The results are expected to be input for future planning for the development of new rice fields in Jatigede Subdistrict, Sumedang Regency. The study was conducted from December 2016 to May 2017. The type of data used consists of primary data and secondary data. Primary data is obtained from direct surveys to the field by conducting ground checks or through interviews. The results showed that the potential land available for the development of new paddy fields in Jatigede sub-district was 3,419 ha and from the potential land area will be developed into new paddy fields of 346 ha (4.18%) spread over 4 (four) villages, ie Cipicung 54 ha, Ciranggem Village covering 94 ha, Cisampih Village covering 107 ha and Karedok Village area of 91 ha. The result of feasibility test on new paddy field development activity in Jatigede subdistrict shows Net Present Value (NPV) is Rp. 92,893,000,000 and Benefit Cost Ratio (B/C) 3.32. Development strategies are: Respectively development strategies comprise (1) Optimize government financing assistance to accelerate the implementation of new paddy field target, (2) Together with the head of the farmer group association assist the paddy field construction process, (3) Conduct a survey of water resources and other supporting infrastructure around paddy field area, (4) Ensuring the new paddy field is not overlapping with other area, (5) Socialize the long-term benefits of the development of new paddy field by getting subsidy for three year since the first year development. (6) Encourage local governments to established immediately as LP2B areas and included in the RTRW of Jatigede District.